Environmental factors influencing older adults' walking for transportation: a study using walk-along interviews - Van Cauwenberg Jelle; Van Holle Veerle; Simons Dorien; Deridder Riet; Clarys Peter; Goubert Liesbet; Nasar Jack; Salmon Jo; De Bourdeaudhuij Ilse; Deforche Benedicte (BMC, 2012)
Abstract Background Current knowledge on the relationship between the physical environment and walking for transportation among older adults (≥ 65 years) is limited. Qualitative research can provide valuable information and inform further research. However, qualitative studies are scarce and fail to include neighborhood outings necessary to study participants' experiences and perceptions while interacting with and interpreting the local social and physical environment. The current study sought to uncover the perceived environmental influences on Flemish older adults' walking for transportation. To get detailed and context-sensitive environmental information, it used walk-along interviews. Methods Purposeful convenience sampling was used to recruit 57 older adults residing in urban or semi-urban areas. Walk-along interviews to and from a destination (e.g. a shop) located within a 15 minutes' walk from the participants' home were conducted. Content analysis was performed using NVivo 9 software (QSR International). An inductive approach was used to derive categories and subcategories from the data. Results Data were categorized in the following categories and subcategories: access to facilities (shops & services, public transit, connectivity), walking facilities (sidewalk quality, crossings, legibility, benches), traffic safety (busy traffic, behavior of other road users), familiarity, safety from crime (physical factors, other persons), social contacts, aesthetics (buildings, natural elements, noise & smell, openness, decay) and weather. Conclusions The findings indicate that to promote walking for transportation a neighborhood should provide good access to shops and services, well-maintained walking facilities, aesthetically appealing places, streets with little traffic and places for social interaction. In addition, the neighborhood environment should evoke feelings of familiarity and safety from crime. Future quantitative studies should investigate if (changes in) these environmental factors relate to (changes in) older adults' walking for transportation.